SUSTAINABLE SOLUTIONS: GREENHOST LEADING THE INDUSTRIAL DAY 6.0 CHARGE - Utik Kuntariati; Luh Eka Susanti; A. A. A. Arun Suwi Arianty; Putu Dian Yuliani Paramita; Ni Made Rinayanthi; I Wayan Suadnyana (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
Sustainable Solutions: Greenhost Leading the Industrial Day 6.0 Charge